2021
DOI: 10.3354/aei00422
|View full text |Cite
|
Sign up to set email alerts
|

Developing payment for ecosystem service schemes for coastal aquaculture in southwestern Taiwan

Abstract: Taiwan’s aquaculture farms are mostly established along intertidal zones and coastal land areas, and their presence may affect coastal ecosystems and their ecosystem services (ESs). Payments for ecosystem services (PES) represent a potential method of enhancing the provision of ESs for coastal aquaculture; thus, their feasibility should be discussed. In this study, we conducted focus group interviews to identify issues and collect information about coastal aquaculture in southwestern Taiwan, and we developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…142 Some studies have suggested that seaweed could be grown at large scale and then sunk to the deep sea to temporarily lock carbon away from the surface, 193 but there are many uncertainties within this approach and more research is required. 142 A range of schemes have been suggested for payment for ecosystem services (PES), [195][196][197] although valuation of ecosystem services is not always financially focused. 198 Nevertheless, of particular interest to many in aquaculture is the use of certified credit schemes, where organisations purchase credits from the aquaculture producers to compensate for, or offset, their own emissions or environmental impacts, whether they are nutrients or carbon.…”
Section: Offsetting With Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…142 Some studies have suggested that seaweed could be grown at large scale and then sunk to the deep sea to temporarily lock carbon away from the surface, 193 but there are many uncertainties within this approach and more research is required. 142 A range of schemes have been suggested for payment for ecosystem services (PES), [195][196][197] although valuation of ecosystem services is not always financially focused. 198 Nevertheless, of particular interest to many in aquaculture is the use of certified credit schemes, where organisations purchase credits from the aquaculture producers to compensate for, or offset, their own emissions or environmental impacts, whether they are nutrients or carbon.…”
Section: Offsetting With Aquaculturementioning
confidence: 99%
“…A range of schemes have been suggested for payment for ecosystem services (PES), 195 , 196 , 197 although valuation of ecosystem services is not always financially focused. 198 Nevertheless, of particular interest to many in aquaculture is the use of certified credit schemes, where organisations purchase credits from the aquaculture producers to compensate for, or offset, their own emissions or environmental impacts, whether they are nutrients or carbon.…”
Section: Review Of Research Articles and Academic Studiesmentioning
confidence: 99%